Phonological Error Analysis of Ngapak Javanese Speakers Reading SurahAl-Nāzi’āt - Naafi Al Kautsar; Eka Dewi Mutiara (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2025)
This study aims to analyze the phonological errors that occur in the pronunciation of Surah An-Nazi'at by speakers of the Javanese Ngapak dialect, particularly among students at TPQ Darul Fallah Pemalang. The Javanese Ngapak dialect is known for its distinct phonological characteristics that differ from Arabic, which can affect the pronunciation of Qur'anic verses. Using a qualitative approach with descriptive analysis methods, this study identifies the forms of phonological errors and their contributing factors. Data were collected from voice recordings of Surah An-Nazi'at recited by 17 students selected through purposive sampling. The results of the study show various phonological errors, such as letter substitution, letter addition, and letter omission. For example, the pronunciation of ع as أ or vice versa, as well as the substitution of س with ث. These errors are caused by the influence of the local dialect, habitual pronunciation influenced by the native language, and a lack of proper practice in pronouncing certain Arabic letters. This study is expected to contribute practically to tajwid teaching and enrich the study of Arabic phonology, particularly concerning the influence of regional dialects on Arabic pronunciation.